Coniferes et polen in situ du Buntsandstein de l'ile de Majorque(Baléares, Espagne) - Álvarez Ramis, c.; Grauvogel-stamm, L. (Cuadernos de Geología Ibérica, 1996)
The morphological study of two male eones from the upper part of the Buntsandstein (Estellencs unit) of the Majorca Island (Balearie Isles, Spain) shows that they belong to the conifer reproductive organ genus Willsiostrobus. The study of their pollen in situ indicates that they have to be attributed to two distinct species. One of them provided pollen grains corresponding to the sporae dispersae Voltziaceaesporites heteromorpha and could be referred to 1V rhomboidalis, a characteristie species of the GrØsÆVoltzia (Upper Buntsandstein) of northeastern France. The other one which was unknown before represents a new species, 1V hexasacciphorus. It is the reproductive organ which produced the hexasaccate pollen corresponding to the sporae dispersae known under two taxons Stellapollenites thiergartii and Hexasaccites muelleri, which also occurs in the GrØsÆVoltzia of the Vosges (France). The occurrence of this pollen type in the Estellenes unit indicates that the upper part of the Buntsandstein in the Majorca Island is Anisian, like the uppermost part of the Upper BuntConifØres et pollen in sita e/u Buntsandstein.. 231 sanstein in the northeastern France where it is represented by the GrØsÆ Voltzia.
Keywords: In situ pollen grains; Conifers; Buntsandstein facies; Middle Triassic (Anisian); Majorca Island (Balearie Isles; Spain)